Climate change and cities : first assessment report of the Urban Climate Change Research Network - Rosenzweig, Cynthia; Cambridge eBooks; Urban Climate Change Research Network (Cambridge : Cambridge University Press, 2011)
Urban areas are home to over half the world's people and are at the forefront of the climate change issue. The need for a global research effort to establish the current understanding of climate change adaptation and mitigation at the city level is urgent. To meet this goal a coalition of international researchers - the Urban Climate Change Research Network (UCCRN) - was formed at the time of the C40 Large Cities Climate Summit in New York in 2007. This book is the First UCCRN Assessment Report on Climate Change and Cities. The authors are all international experts from a diverse range of cities with varying socio-economic conditions, from both the developing and developed world. It is invaluable for mayors, city officials and policymakers; urban sustainability officers and urban planners; and researchers, professors and advanced students.
Foreword / Anna Tibaijuka -- Foreword / Rajendra Kumar Pachauri -- Foreword / Michael R. Bloomberg -- Foreword / Jeffrey D. Sachs -- pt. I Introduction : Urban climate change in context -- pt. II Defining the risk framework : Cities, disasters, and climate risk -- Urban climate : processes, trends, and projections -- pt. III Urban sectors : Climate change and urban energy systems -- Climate change, water, and wastewater in cities -- Climate change and urban transportation systems -- Climate change and human health in cities -- pt. IV Cross-cutting issues : The role of urban land in climate change -- Cities and climate change : the challenges for governance -- Conclusion : Moving forward -- Appendix A : City case studies and topics in vulnerability, adaptation, and mitigation -- Appendix B : Acronyms and abbreviations -- Appendix C : Steering group, ARC3 authors, and reviewers.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Urban ecology (Sociology); Climatic changes -- Risk management; Climate change mitigation; Urban policy; Electronic books